Digital Inclusion Evaluation: A User Experience Study of Praja Mobile among Elderly and Adult Users - Ida Ayu Agung Yogi Pradnyani; Made Dandy Nugraha Gunarsa; Yuvensius Hugolinus Haman; Gede Rasben Dantes; Gede Indrawan; I Made Agus Oka Gunawan (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2026)
This study aims to evaluate the user experience of the Praja Mobile application among two age groups, namely adults and elderly users, as an effort to assess the level of digital inclusion. The research employed a quantitative descriptive approach using the User Experience Questionnaire (UEQ) instrument, which measures six main aspects: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. The study involved 40 respondents, consisting of 20 adult users and 20 elderly users. Based on the analysis results, the elderly group achieved scores of 2.00 for attractiveness, 1.88 for efficiency, 1.76 for dependability, 1.75 for stimulation, 1.82 for perspicuity, and 0.78 for novelty. Meanwhile, the adult group obtained scores of 2.30 for attractiveness, 2.30 for efficiency, 2.05 for dependability, 2.07 for stimulation, 2.03 for perspicuity, and 0.72 for novelty. The most notable difference was observed in the perspicuity aspect. This finding indicates that elderly users still experience difficulties in understanding the application’s navigation and usage flow compared to adult users. The implications of this study emphasize the importance of designing interfaces that are more elderly-friendly, particularly in improving information clarity, navigation structure, and ease of interaction. Therefore, the findings of this study contribute practical recommendations for application developers to support greater digital inclusion, enabling applications to be more accessible across different age groups.